PROYEKSI KERAWANAN BANJIR PADA LAHAN SAWAH BERBASIS MODEL IKLIM HadCM3 DI DAS BILA PROVINSI SULAWESI SELATAN - A Abdullah; Risna Hardianty Haedar; Annas Boceng; Reza Asra (JURNAL GALUNG TROPIKA, 2022)
Sidenreng Rappang Regency is the center for developing rice production in South Sulawesi and is included in the Bila River Basin (DAS). Sidenreng Rappang, in the last five years, has experienced flooding every year, especially in Pitu Riawa District, Dua Pitue District, and Pitu Riase District. This study aims to project rainfall changes and vulnerability to flooding based on the HadCM3 climate model in the Bila watershed area. Analysis of changes in rainfall based on the HadCM3 climate prediction model with a short-term baseline (10 years). Data were analyzed spatially by scoring the parameters of flood vulnerability and validated through surveys and field observations. Data for each parameter is overlaid using a geographic information system (GIS). The actual flood vulnerability classification results were projected using the HadCM3 climate model and produced a flood hazard projection map with the HadCM3 model for the Bila watershed area. The HadCM3 model prediction shows an increase in rainfall from April to October, and high-intensity precipitation occurs in May, June, and July. The actual level of flood hazard in paddy fields in the Bila watershed area is classified as very high, with an area of 22,339.44 ha (56.75%), and the HadCM3 Climate Model projection is classified as high with an area of 25,260.71 ha (64.17%). Paddy fields in the Bila watershed have a high level of flood vulnerability.